Impaired Thermogenesis and a Molecular Signature for Brown Adipose Tissue in Id2 Null Mice. (10th April 2016) - Zhou, Peng; Robles-Murguia, Maricela; Mathew, Deepa; Duffield, Giles E.
Abstract : Inhibitor of DNA binding 2 (ID2) is a helix-loop-helix transcriptional repressor rhythmically expressed in many adult tissues. Our previous studies have demonstrated that Id2 null mice have sex-specific elevated glucose uptake in brown adipose tissue (BAT). Here we further explored the role of Id2 in the regulation of core body temperature over the circadian cycle and the impact of Id2 deficiency on genes involved in insulin signaling and adipogenesis in BAT. We discovered a reduced core body temperature in Id2 −/− mice. Moreover, in Id2 −/− BAT, 30 genes including Irs1, PPAR s, and PGC-1 s were identified as differentially expressed in a sex-specific pattern. These data provide valuable insights into the impact of Id2 deficiency on energy homeostasis of mice in a sex-specific manner.